In-vehicle air quality in public buses during real-world trips in Kathmandu Valley, Nepal - Anu Shrestha; Narayan Babu Dhital (Environmental Challenges)
Urban air quality shows notable variability across various microenvironments. Transport-related microenvironments often have one of the highest air pollution levels, where commuters have significant exposure to air pollutants. In Kathmandu Valley (KV), Nepal, passengers’ exposure to air pollutants in such microenvironments remain a poorly understood issue. In this study, we analyzed cabin air quality and ventilation rates in public buses operated in KV. In-cabin and in-route ambient air pollution levels were monitored during real-world bus operations in 32 trips on a test route selected in the core city area. A CO2 mass balance model was applied to estimate cabin ventilation rates. The mean in-cabin and outdoor PM2.5 concentrations were 95.9 ± 40.4 (mean ± standard deviation) and 94.7 ± 32.4 μg/m3, respectively. Likewise, mean in-cabin and outdoor PM1 concentrations were 72.5 ± 31.3 and 69.7 ± 25.3 μg/m3, respectively, with mean PM1 to PM2.5 ratio >0.75, indicating that a majority of particle mass was in the sub-micron size range, which is often more health-hazardous. We estimated passengers’ inhalation dose for PM2.5 and PM1 as 5.65 ± 2.32 and 4.27 ± 1.79 μg/km, respectively. Among various factors considered, traffic hour significantly affected both in-cabin and ambient particulate matter concentrations. The trip-average in-cabin CO2 concentration ranged from 513 to 1230 ppm, whereas cabin ventilation rates ranged from 8.0 to 72.4 L/s/person. Ventilation levels in a majority of bus trips were inadequate, especially considering the recommended thresholds to reduce the transmission risk of airborne diseases. Setting standards for ventilation and air conditioning systems in public buses is crucial to ensure thermal comfort, protect bus commuters from the harmful impacts of air pollution, and to improve public transport services in KV.